Feeder cells treated with ethanol can be used to maintain self‐renewal and pluripotency of human pluripotent stem cells. Issue 2 (4th January 2023) - Ren, Yahui; Zhang, Sijin; Liang, Yun; Gong, Zichao; Cui, Yongyi; Song, Wei
Abstract : Feeder cells play an important role in the culture of human pluripotent stem cells (hPSCs) in vitro . Previously, we used methanol as a fixative to prepare feeder cells for the cultivation of pluripotent stem cells (PSCs), and this method could maintain the self‐renewal and pluripotency of PSCs. However, methanol is toxic, and so here we examined whether ethanol could be used to prepare feeder cells as a fixative for hPSC culturing. Primed, naïve, and extended human embryonic stem cells and induced pluripotent stem cells can maintain self‐renewal and undifferentiated potential on feeder cells treated with ethanol for an extended period. RNA sequencing analysis showed that the expression of collagen‐related genes in hPSCs cultured on feeder cells treated with ethanol was significantly lower as compared with hPSCs cultured on feeder cells treated with mitomycin C. Therefore, we speculate that the signaling pathway mediated by collagen‐related genes may, at least in part, contribute to the maintenance of self‐renewal and pluripotency of PSCs induced by feeder cells treated with chemicals. Abstract : Human fibroblasts can be used as feeder cells after treatment with ethanol. Primed, naïve and extended hPSCs can maintain the self‐renewal and undifferentiated potential on feeder cells treated with ethanol. Collagen‐related genes in pluripotent stem cells cultured on feeder cells treated with ethanol may contribute to the maintenance of the pluripotent state of pluripotent stem cells.